Identification of Usability Issues in the ELLS Website at Amikom University Purwokerto - Debby Ummul Hidayah; Abdul Azis; Tyas Pratama Puja Kusuma; Irma Darmayanti (Universitas Islam Indragiri, 2026)
The transformation of information technology has significantly influenced the education sector, particularly in the implementation of online learning. One of its key contributions is enabling lecturers and students to interact through e-learning platforms without the constraints of time and space. Amikom University Purwokerto, as one of the higher education institutions, has developed an e-learning platform called ELLS. Based on observational analysis, several issues are frequently encountered by users, including confusion in navigation, difficulty in locating information, repeated uploading of course materials for the same subject across multiple classes, the absence of notification messages, unexpected system logouts during grading activities, and a visually unappealing interface. To further investigate usability issues in the ELLS website, Nielsen’s heuristic evaluation method—consisting of 10 principles—was applied. The findings reveal that, out of 8 main features tested, a total of 19 usability issues were identified. The most frequently occurring problems are related to the principles of visibility of system status, user control and freedom, and consistency and standards across interface elements. One critical issue with a severity level of 4 (usability catastrophe) was identified in the assignment grading feature, which poses a risk of sudden loss of student grade data. In addition, 15 issues were categorized with severity level 3 and 3 issues with severity level 2. These findings indicate that although the ELLS system is functionally operational, there are still numerous interface design aspects that need improvement to enhance efficiency, clarity, and user comfort, particularly for lecturers and students as the primary users.